Acute Acalculous Cholecystitis Associated with Severe Malaria – A Case Report - Oliveira, Teresa; Dinis, Ana Clara; Narciso, Sofia; Pereira, Tiago; Catorze, Nuno (Brazilian Journal of Case Reports, 2025)
We present the case of a 29-year-old male diagnosed with severe malaria admitted to the Intensive Care Medicine Service. While undergoing treatment with quinine dihydrochloride and doxycycline, he developed an acute case of acalculous cholecystitis on the fourth day. Conservative treatment with antibiotic therapy was performed, and the patient showed favorable progression. Gastrointestinal complications associated with malaria are common; however, acute acalculous cholecystitis linked to malaria is an extremely rare complication, scarcely described in the literature, and its evolution can be catastrophic.